2020
DOI: 10.1371/journal.pone.0242534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of COVID-19 hospitalized patients

Abstract: Clinical and molecular characterization by Whole Exome Sequencing (WES) is reported in 35 COVID-19 patients attending the University Hospital in Siena, Italy, from April 7 to May 7, 2020. Eighty percent of patients required respiratory assistance, half of them being on mechanical ventilation. Fiftyone percent had hepatic involvement and hyposmia was ascertained in 3 patients. Searching for common genes by collapsing methods against 150 WES of controls of the Italian population failed to give straightforward st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…11p15.5) was associated with influenza severity and mortality, and faster progression of HIV infection towards AIDS [ 125 , 126 , 127 , 128 ]. As regards COVID-19, the rs12252 (C) allele is considered a risk variant [ 120 ], especially as regards the homozygosity for the C allele, i.e., the (CC) genotype, in symptomatic cases [ 118 , 129 ]. As discussed in the previous sections, the adoption of uniform criteria to describe disease severity and the careful choice of the compared groups/populations are essential in order to obtain reproducible results.…”
Section: Other Immune Response Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…11p15.5) was associated with influenza severity and mortality, and faster progression of HIV infection towards AIDS [ 125 , 126 , 127 , 128 ]. As regards COVID-19, the rs12252 (C) allele is considered a risk variant [ 120 ], especially as regards the homozygosity for the C allele, i.e., the (CC) genotype, in symptomatic cases [ 118 , 129 ]. As discussed in the previous sections, the adoption of uniform criteria to describe disease severity and the careful choice of the compared groups/populations are essential in order to obtain reproducible results.…”
Section: Other Immune Response Genesmentioning
confidence: 99%
“…By whole exome sequencing and unbiased collapsing gene analysis, an Italian study identified PRKRA as one of the two protective genes (see below) comparing hospitalized COVID-19 patients with controls of unknown status. In this context, the deleterious variant was more frequent in COVID-19 patients than in controls [ 120 ].…”
Section: Other Immune Response Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently there is little information on the clinical presentation of and outcomes in Latin America, especially in hospitalized patients (6)(7)(8)(9). This could contrast with that reported in countries of the northern hemisphere, which have dissimilar features on demographic, economic, cultural, healthcare systems and/or mitigation strategies issues (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). We present this preliminary report on a cohort of patients during the first wave in a southern region in Chile detailing clinical features and outcomes in a reference center.…”
Section: Introductionmentioning
confidence: 97%